The Influence of Local Actors in the Empowerment of Smallholder Livestock Farming Communities - Muladno; Andraini Agatha, Melfa; Sjaf, Sofyan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
The success of the empowerment program in the School for Smallholder Livestock Farming Community (SPR) cannot be separated from the contribution of local actors who have a dominant role in the community. This study aims to identify the local actors who dominate the empowerment of smallholder livestock farming community programs, measures the influence index and capital ownership as well as the social actions of these actors in carrying out their roles located. This research took place in two areas, namely Cinta Damai Village, Sungai Lilin District, Musi Banyuasin Regency, South Sumatera Province and Soko Village, Temayang District, Bojonegoro Regency, East Java Province. This reasearch was carried out using a mixed-method, quantitative and qualitative approach. The results showed that there were six dominant local actors in SPR empowerment. Four of them are activists who play an active role in the SPR community, and the other two actors are village government officials. The educational background and experience of actors in different villages influence the actions and strategies in the arena of SPR empowerment. Institutional and moral capital is the highest capital used by actors in Cinta Damai Village. In contrast, moral capital and economic capital are the highest capital used by actors in Soko Village.